High‐dose melphalan‐based sequential conditioning chemotherapy followed by allogeneic haematopoietic stem cell transplantation in adult patients with relapsed or refractory acute myeloid leukaemia. (21st February 2018) - Steckel, Nina K.; Groth, Christoph; Mikesch, Jan‐Henrik; Trenschel, Rudolf; Ottinger, Hellmut; Kordelas, Lambros; Mueller‐Tidow, Carsten; Schliemann, Christoph; Reicherts, Christian; Albring, Joern C.; Silling, Gerda; Schmidt, Eva; et al.
Summary: Considering the unsatisfactory results of salvage therapies for patients with relapsed/refractory acute myeloid leukaemia (R/R‐AML), their value before allogeneic haematopoietic stem cell transplantation (HSCT) remains questionable. However, direct allogeneic HSCT following established conditioning regimens applied in patients with R/R‐AML during active disease has been equally disappointing. In this retrospective observational study, high‐dose melphalan, as part of a sequential preparative regimen, followed by a total body irradiation (4 × 2 Gy)‐based or a treosulfan‐based dose‐adapted conditioning therapy for allogeneic HSCT was administered to 292 adult patients (median age 56 years, range 17–74) with primary refractory (144 patients), secondary refractory (97 patients) or relapsed AML (51 patients). Overall survival rates at 3 years were 34%, 29% and 41%, respectively. Risk factors associated with an inferior survival were higher age, transplantation from a human leucocyte antigen‐mismatched donor and high disease burden. Patients transplanted with blast infiltration <20% showed a notable survival rate of 51% at 3 years. In particular, patients with primary refractory AML showed a more favourable outcome when transplanted early during their disease course. Thus, high‐dose melphalan‐based sequential conditioning chemotherapy followed by an allogeneic HSCT is feasible and enables long‐term remission to be achieved in a substantial proportion of patients with active R/R‐AML.